Thought and world: An austere portrayal of truth, reference, and semantic correspondence - Hill, Christopher S (c., 2013)
The author presents a deflationary theory of the content of semantic notions. He represents a broad range of these notions as being free from substantive metaphysical and empirical presuppositions. He also seeks to explain the intuition that there is a relation of mirroring or semantic correspondence linking thoughts to reality.